2018
DOI: 10.1037/rev0000108
|View full text |Cite
|
Sign up to set email alerts
|

Don’t blame the model: Reconsidering the network approach to psychopathology.

Abstract: Citation for published version (APA): Bringmann, L. F., & Eronen, M. I. (2018). Don't blame the model: Reconsidering the network approach to psychopathology. Psychological Review, 125(4), 606-615. https://doi.org/10.1037/rev0000108 Copyright Other than for strictly personal use, it is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), unless the work is under an open content license (like Creative Commons).Take-down policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
163
0
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(183 citation statements)
references
References 106 publications
(214 reference statements)
4
163
0
6
Order By: Relevance
“…symptoms) are presumed to cause any latent factor rather than the other way around (Fried et al, 2016), would allow us to weight the contribution of symptoms to the sum score based on their network centrality. This type of formative sum score has already been utilized (Boschloo et al, 2016) and may allow us to better represent the phenomenology of depression than using either method in isolation (Bringmann & Eronen, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…symptoms) are presumed to cause any latent factor rather than the other way around (Fried et al, 2016), would allow us to weight the contribution of symptoms to the sum score based on their network centrality. This type of formative sum score has already been utilized (Boschloo et al, 2016) and may allow us to better represent the phenomenology of depression than using either method in isolation (Bringmann & Eronen, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there is a debate, among experts in the field, on the extent to which NA should be used as an additional analytic tool to explore constellations of elements (signs, symptoms, stressors, etc.) rather than using it as a tool to criticize diagnostic systems [57, 101]. In this vein, as the Clinimetrics approach has repeatedly emphasized, the analysis of psychopathology exceeds the framework of self-reported symptoms as it should also include other important parameters, for instance, functional capacity, rate of progression of the disorder (staging), responses to other treatments, or even biomarkers [15, 102] and all this information should ultimately incorporate clinicians’ judgments to estimate the clinical utility of it [5].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that central elements of psychopathology networks have high clinical relevance (Boschloo, van Borkulo, Borsboom, & Schoevers, ; Christensen, Kenett, Aste, Silvia, & Kwapil, ; Rodebaugh et al, ). However, centrality indices have been originally developed for social networks and might not be adequate to capture the type of relationships encoded by psychological networks (Bringmann & Eronen, ). Therefore, in addition to centrality, we estimated also the predictability of each node, an index that has been developed specifically for psychological networks (Haslbeck & Waldorp, ).…”
Section: Network Analysesmentioning
confidence: 99%